Two-stage permanent deactivation of the boron-oxygen-related recombination center in crystalline silicon. (September 2017) - Steckenreiter, Verena; Walter, Dominic C.; Schmidt, Jan
Abstract: We analyze the lifetime evolution during permanent deactivation of the boron-oxygen-related defect center (BO defect) in boron-doped, oxygen-rich Czochralski-grown silicon (Cz-Si). In particular, we examine the impact of the samples' states prior to the permanent deactivation process. Samples that were initially fully degraded show a two-stage deactivation process consisting of a fast and a slow deactivation component, which can be fitted by two exponential functions with their respective rate constants. For both components, we find a pronounced increase of the rate constants with illumination intensity. In addition, we observe that the rate constant describing the slow deactivation component of samples deactivated after complete degradation is identical to the rate constant determined on samples, which were deactivated immediately after annealing in darkness. In the latter case, a purely mono-exponential deactivation behavior was observed. Our study clearly demonstrates that the asymptotic deactivation behavior does not depend on the initial state of the lifetime sample. We prove that the same is valid for initially degraded and dark-annealed PERC solar cells. Hence, it is not necessary to first degrade the sample to realize a fast BO deactivation.